2002
DOI: 10.1080/09670870110118713
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect influences of the weaver ant Oecophylla smaragdina on citrus farmers' pest perceptions and management practices in the Mekong Delta, Vietnam

Abstract: In the Mekong Delta, Vietnam, the predatory weaver ant Oecophylla smaragdina was abundant in about 75% of the sweet orange and 25% of the Tieu mandarin orchards. With a three-level scale (low, moderate, high), farmers assessed the incidence, severity and yield loss of fruit caused by major pests. With abundant O. smaragdina, sweet orange farmers assessed a lower pest infestation or yield loss for the citrus stinkbug Rhynchocoris humeralis, the aphids Toxoptera aurantii and T. citricidus, the leaf-feeding cater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…To illustrate their effectiveness as biological control agents, Dejean (1991) demonstrated that a colony comprising 12 nests may capture about 45,000 prey per year. Oecophylla smaragdina (Fabricius) successfully protects plants against insect herbivores (Van Mele et al 2002), including fruit flies in commercial mango plantation in northern Australia (Peng and Christian 2006). Likewise, the African weaver ant O. longinoda (Latreille) significantly reduces fruit fly infestation, damage being negatively correlated with the number of ant nests in the mango trees (Van Mele et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…To illustrate their effectiveness as biological control agents, Dejean (1991) demonstrated that a colony comprising 12 nests may capture about 45,000 prey per year. Oecophylla smaragdina (Fabricius) successfully protects plants against insect herbivores (Van Mele et al 2002), including fruit flies in commercial mango plantation in northern Australia (Peng and Christian 2006). Likewise, the African weaver ant O. longinoda (Latreille) significantly reduces fruit fly infestation, damage being negatively correlated with the number of ant nests in the mango trees (Van Mele et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…A weaver ant technology using weaver ants as a key element has been implemented to control the major insect pests by cashew growers in Australia , Papua New Guinea (Peng 1999(Peng , 2000, East Timor (Amaral 2010), and Mozambique (Peng 2002). Weaver ants, O. smaragdina, are widely distributed in tropical areas of south-east Asia and northern Australia (Lokkers 1986), and they are abundant in Vietnam (Van Mele et al 2002). Weaver ants have been used to control citrus insect pests on the Mekong delta in Vietnam for many years (Van Mele et al 2002), but the role of the ants in cashew orchards has not been explored.…”
mentioning
confidence: 99%
“…Wylie 1974;Macfarlane et al 1976;Lim and Kirton 2003;Peng et al 2010aPeng et al , 2011bPeng et al , 2012 and in horticultural crops (e.g. Stapley 1972;Huang and Yang 1987;Van Mele et al 2002;Peng et al 2004Peng et al , 2010bPeng and Christian 2005a). The effectiveness of weaver ants in biological control has been Australian Forestry, 2013Vol.…”
Section: Introductionmentioning
confidence: 96%